2020
DOI: 10.3390/ijerph17176119
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Linear Sprint, Lower-Body Power Output and Change of Direction Performance in Elite Soccer Players

Abstract: The aim of this study was to investigate the relationship between linear sprint, power output obtained during a squat and change of direction (COD) performance. Fifteen elite soccer players participated in this study (age = 21.7 ± 0.72 years, body mass = 74.9 ± 9.11 kg, body height = 180.4 ± 7 cm, training experience = 9 ± 1.5 years). To examine these correlations a following battery of tests were carried out: 20-m linear sprint, one-repetition maximum (1RM) squat strength, peak power output obtained during a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The test was repeated when the player did not touch the base of the cone with his/her hand, crossed his/her feet while shuffling sideways, or failed to face forward throughout. The running tests were measured by a set of photocells (Witty, Microgate, Bolzano, Italy), which was used to record the time of running tests in other authors’ research [ 35 , 36 ]. The tests were started from a standing position with feet placed 0.3 m before the starting line with the first photocells gate.…”
Section: Methodsmentioning
confidence: 99%
“…The test was repeated when the player did not touch the base of the cone with his/her hand, crossed his/her feet while shuffling sideways, or failed to face forward throughout. The running tests were measured by a set of photocells (Witty, Microgate, Bolzano, Italy), which was used to record the time of running tests in other authors’ research [ 35 , 36 ]. The tests were started from a standing position with feet placed 0.3 m before the starting line with the first photocells gate.…”
Section: Methodsmentioning
confidence: 99%
“…Accelerations require an increase in momentum to propel the body in a new direction ( Spiteri et al, 2015 ). Decelerations involve braking mechanisms that induce stressful loading to the posterior tissues ( Papla et al, 2020 ). In this investigation, athletes executed over 500 accelerations and decelerations in the different speed zones per training session.…”
Section: Discussionmentioning
confidence: 99%
“…Mostly small and moderate correlations were found between linear speed (LS) and change of direction deficit (CODD). A limited number of studies have analyzed the relationship between linear sprint (LS) and change of direction deficit (CODD) among team sports (Loturco et al, 2018(Loturco et al, , 2020Papla et al, 2020;Rouissi et al, 2016). Our results are in line with the findings of Papla et al (2020), where the authors showed that 20-m linear sprint time was not significantly correlated with COD deficit in two different tests.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of studies have analyzed the relationship between linear sprint (LS) and change of direction deficit (CODD) among team sports (Loturco et al, 2018(Loturco et al, , 2020Papla et al, 2020;Rouissi et al, 2016). Our results are in line with the findings of Papla et al (2020), where the authors showed that 20-m linear sprint time was not significantly correlated with COD deficit in two different tests. On the contrary, Loturco et al (2018) registered a statistically significant correlation between COD deficit and 10 m flying start linear sprint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation